Automated River Reach Definition Strategies: Applications for the Surface Water and Ocean Topography Mission. Issue 10 (11th October 2017) - Frasson, Renato Prata de Moraes; Wei, Rui; Durand, Michael; Minear, J. Toby; Domeneghetti, Alessio; Schumann, Guy; Williams, Brent A.; Rodriguez, Ernesto; Picamilh, Christophe; Lion, Christine; Pavelsky, Tamlin; Garambois, Pierre‐André
Abstract: The upcoming Surface Water and Ocean Topography (SWOT) mission will measure water surface heights and widths for rivers wider than 100 m. At its native resolution, SWOT height errors are expected to be on the order of meters, which prevent the calculation of water surface slopes and the use of slope‐dependent discharge equations. To mitigate height and width errors, the high‐resolution measurements will be grouped into reaches (∼5 to 15 km), where slope and discharge are estimated. We describe three automated river segmentation strategies for defining optimum reaches for discharge estimation: (1) arbitrary lengths, (2) identification of hydraulic controls, and (3) sinuosity. We test our methodologies on 9 and 14 simulated SWOT overpasses over the Sacramento and the Po Rivers, respectively, which we compare against hydraulic models of each river. Our results show that generally, height, width, and slope errors decrease with increasing reach length. However, the hydraulic controls and the sinuosity methods led to better slopes and often height errors that were either smaller or comparable to those of arbitrary reaches of compatible sizes. Estimated discharge errors caused by the propagation of height, width, and slope errors through the discharge equation were often smaller for sinuosity (on average 8.5% for the Sacramento and 6.9% for the Po) and hydraulic control (Sacramento: 7.3% and Po: 5.9%) reaches than for arbitrary reaches of comparable lengths (Sacramento: 8.6% and Po: 7.8%). This analysis suggests that reach definition methods that preserve the hydraulic properties of the river network may lead to better discharge estimates. Key Points: Choice of river segmentation strategies affect the quality of reach‐averaged products produced by remote sensing Reach definition methods based on hydraulic properties of rivers appear to lead to better discharge than reaches of arbitrary lengths Method for the detection of unlisted hydraulic structures compatible with future SWOT data are proposed and tested